The effects of antihypertensive drugs and antioxidant supplement on the development and progression of hypertension, renal oxidative stress and damage in spontaneously hypertensive rats - Govindasamy , Chandran (2017)
Oxidative stress has been implicated in the development and progression of hypertension and subsequent organ damage including the kidneys. However the effect of antihypertensive drugs or antioxidant supplementation on renal oxidative stress during the development and progression of hypertension and the subsequent renal damage has not been well studied. The present study was undertaken to look into the effect of certain antihypertensive drugs with known antioxidant properties as well as antioxidants on renal oxidative stress during the development and progression of hypertension and the subsequent renal damage. The study was performed using spontaneously hypertensive rats (SHR) as well as N-nitro-L-arginine methyl ester (LNAME) induced nitric oxide (NO) deficient hypertensive Wistar-Kyoto (WKY) and SHR rats in comparison with normotensive WKY rats. The first phase study consisted of a time course study on changes in systolic blood pressure (SBP), body morphometric parameters and renal oxidative stress status in SHR from the age of 4 weeks until 64 weeks, followed by the study on L-NAME induced NO deficient hypertensive WKY and SHR rats involving observation of these parameters at the time points of 4 weeks of age (prehypertension), 16 weeks of age (established hypertension) and 28 weeks of age (occurrence of renal damage). The second and third phase studies were intervention based studies which looked into the effect of antihypertensive drugs and antioxidants on these parameters during the development and progression of hypertension and the subsequent renal damage. The first phase studies showed that SHR became hypertensive by the age of 8 weeks, with the SBP increasing gradually until 64 weeks of age. SHR developed renal damage and renal oxidative stress from the age of 24 weeks, which worsened gradually until the age of 64 weeks in line with increasing hypertension. Correlation studies suggest a strong relationship between renal oxidative stress with SBP and renal damage. The results also indicate that oxidative stress is a consequence of hypertension and not a cause of it, however it appears to play a prominent role in the maintenance of hypertension and development of renal damage. Renal NOx levels in the SHR decreased from the age of 32 weeks, which occurred together with worsening hypertension and also after oxidative stress and renal damage had commenced from week 24, indicating that the decrease in NO levels occurs as the chronic renal damage in SHR progresses. This suggests that in the SHR, increased renal oxidative stress and reduced NO bioavailability accompanies hypertension and contributes to its maintenance and progressive damage of the kidneys. Studies on the L-NAME induced hypertensive WKY and SHR rats showed that at 28 weeks of age, SHR+L-NAME rats had the highest SBP, renal damage, renal oxidative stress and reduced NOx levels, followed by SHR and WKY+L-NAME rats. This suggests a strong relationship between renal oxidative stress and reduced NO bioavailability with hypertension and renal damage. The second phase study confirmed the hypotensive effect of clonidine, enalapril and amlodipine. Enalapril had the greatest hypotensive effect as it was able to reduce SBP in SHR to normotensive levels while clonidine and amlodipine were not able to. All three drugs showed antioxidant capabilities as they were able to reduce renal oxidative stress. Enalapril appeared to have the highest antioxidant capacity with amlodipine having the least. All three drugs xxxvi showed renoprotective properties with enalapril having the highest renoprotective effect and amlodipine having the least effect. Enalapril was able to fully restore the reduced renal NOx levels in all three hypertensive groups. Clonidine was only able to significantly increase NOx levels in SHR+C and SHR+C+L-NAME rats while amlodipine was not able to increase renal NOx levels in any of the hypertensive animal groups. These results suggest that the physiological mechanisms involved in the hypotensive and renoprotective properties of enalapril and clonidine might involve NO metabolism. Results from this phase of study suggest that the renoprotective and hypotensive properties of these antihypertensive drugs are associated with its antioxidant capacity, with enalapril showing the greatest hypotensive and renoprotective property as well as antioxidant capacity. The third phase study showed that the antioxidant supplements N-acetylcysteine (NAC), alpha-lipoic acid (ALA) and aqueous neem leaves extract (ANLE) had hypotensive effect but were unable to reduce SBP to levels below 140 mm Hg in any of the hypertensive animal groups. NAC and ALA showed moderate hypotensive effect while ANLE only showed slight hypotensive effect. All three supplements showed significant renoprotective property, whereby NAC and ALA showed moderate renoprotective property while ANLE only had slight renoprotective property. All three supplements were able to reduce renal oxidative stress whereby NAC appeared to have slightly higher effect than ALA with ANLE having the lowest effect. NAC was also able to significantly increase the reduced renal NOx levels in WKY+NAC+L-NAME and SHR+NAC+L-NAME rats, while both ALA and ANLE did not increase the depressed NOx levels in any of the hypertensive rat groups. This result suggests that the physiological mechanisms involved in the hypotensive and renoprotective properties of NAC might involve NO metabolism. Overall the results obtained suggest that NAC and ALA have moderate hypotensive, renoprotective and antioxidant properties while ANLE has only slight degree of these properties. In conclusion, this study showed that both the antihypertensive drugs and the antioxidant supplements that were investigated , had hypotensive, renoprotective as well as antioxidant properties. However the antihypertensive drugs showed a much higher degree of these properties compared to the antioxidant supplements.